STRUKTUR NARATIF CERITA NABI KHIDIR DALAM AL-QUR’AN (Adabiyyāt: Jurnal Bahasa dan Sastra, 2011)
This article aims at studying narrative structure of the story of Saint Khidir (Nabi Khidir) in the Koran by questioning its meaning, its structure and  fuction. The narrative approach is used in examining the story. It turns out that like any other stories in the Koran, the story of saint Khidir has a simple structure of narrative (ijaz).  The narrative structure of the story aims at strengthening the faith to Alloh through its thematic values. The story also informs us the social context of the given time and prophet Mohammad’s psychological realm in his preaching. The story gives tremendous moral value to Arabic society in giving meaning to their selves and their surroundings.